Mid-term Outcomes of Endovascular Management of Infective Native Abdominal Aortic Aneurysms - Victor Bilman; Asher Rottenberg; Ilan Davidov; Sarit Malayev; Moshe Halak; Daniel Silverberg (Journal of Endovascular Therapy, 2026)
Introduction: To evaluate outcomes of endovascular aneurysm repair (EVAR) for infective native abdominal aortic aneurysms (INAAA) and to describe microbiological, imaging, and inflammatory findings, as well as the role of prolonged antibiotic therapy and fluorine-18 fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-FDG PET-CT) in follow-up. Methods: This retrospective single-center experience included all patients diagnosed with INAAA and treated with EVAR at our institution between 2020 and 2025. Demographics, microbiology, inflammatory markers, imaging characteristics, technical outcomes, and follow-up data were analyzed. Descriptive statistics were used, and paired continuous variables were compared using the Wilcoxon signed-rank test. Results: Among 494 patients treated for abdominal aortic aneurysm, 12 (2.4%) presented with INAAA. Median age was 75 years (interquartile range [IQR], 69-77), and 83% were male. Salmonella species were identified in 50% of cases. Median white blood cells count at admission was 12.5 × 10 9 /L (IQR, 8.5-14.3), decreasing to 8.8 × 10 9 /L at discharge ( P = .26). C-reactive protein decreased significantly from 141.7 mg/L (IQR, 116.6-263.9) to 24.8 mg/L (IQR, 16.1-92.3; P = .002). All aneurysms were infrarenal, with a median diameter of 48 mm (IQR, 37-51); imaging features included periaortic soft-tissue mass in all patients, saccular morphology in 6 patients, and rapid aneurysm expansion in 4 patients. Technical success was 100%. One patient developed acute kidney injury, and another died from mesenteric ischemia (8.3%). Median follow-up (FU) was 23.8 months (IQR, 5.9-52.8). Complete sac regression occurred in 9 of 11 (81.8%) cases, and the median time to visual PET-CT assessment demonstrating resolution of abnormal FDG uptake was 6.3 months (IQR, 3.9-15.5). Median time of antibiotic treatment was 14.6 months (IQR, 5.4-30.1). Five patients remained on antibiotic therapy, while 3 had it safely discontinued after more than 1 year. During FU, no reinterventions were recorded, and 3 deaths were observed, all non-aortic related. Conclusion: Endovascular aneurysm repair for INAAA achieved high technical success and durable mid-term infection control. C-reactive protein normalization, PET-CT negativity, and sac regression supported bacterial eradication. Extended but finite antibiotic therapy may be adequate in selected, well-monitored patients. Clinical Impact Endovascular aneurysm repair (EVAR) offers an effective and less invasive treatment option for infective native abdominal aortic aneurysms (INAAA), traditionally associated with high morbidity and mortality after open repair. In this series, EVAR achieved complete technical success and durable infection control, supported by rapid CRP decline, sac regression, and PET-CT normalization. Identifying a potential infection focus and maintaining close collaboration between vascular and infectious disease teams were essential to favorable outcomes. These results reinforce EVAR as a safe, durable, and clinically meaningful strategy for selected patients with INAAA when coupled with prolonged, carefully monitored antibiotic therapy.